The Role of OCT in Determining the Location of Extraocular Muscles! - Erkinovich, Kasimov Rayim (American Journal of Bioscience and Clinical Integrity, 2025)
An eye examination can be performed using standard equipment, such as an ophthalmoscope; a more thorough examination requires specialized equipment and a report from a qualified ophthalmologist. The history includes questions about the location, onset, rate of progression, and duration of current symptoms; the presence and nature of pain, discharge, and redness of the eye; and changes in visual acuity. In addition to vision loss and pain, warning signs may include flashing lights and floaters (both of which may indicate retinal detachment), double vision, and loss of peripheral vision.